Development of student activities worksheet based on a comic with 4C in chemical equilibrium for class xi high school - Sri Haryati; Erviyenni Erviyenni; Manju Andika Putri; Sri Wilda Albeta (Jurnal Pendidikan Kimia (JPKim), 2019)
Research on the development of comic-based student activity worksheets (LKPD) with a 4C approach (Critical Thinking, Collaboration, Creativity and Communication) on chemical equilibrium material for high school is an innovation in the development of teaching materials in order to achieve the demands of 21st century learning that facilitates and inspire students to be able to think critically, communicatively, creatively, innovatively, and collaboratively. The study was designed using research and development design (R & D) with a 4-D development model. The validation sheet and user response questionnaire are research instruments designed and then analyzed and produce data in the form of assessment and suggestions by the validator team, teacher respondents and students. Feasibility aspects of content, language, presentation, graphics, and characteristics of comics with a 4C approach with an overall percentage score of 93% by the material validator. The results of the percentage of users by teachers are 95% and the percentage of students is 88% with very good criteria. Based on the data analysis, it can be concluded that student activities worksheets based on comics with a 4C approach that produced is valid and can be used on Senior High School on chemical equilibrium material.Keywords:Chemical equilibrium; student activities sheet based comics with 4C approach; 4-D development model